Body mass index, C-reactive protein, and pancreatic cancer: A Mendelian randomization analysis to investigate causal pathways - Li, Zhenqi; Jin, Liquan; Xia, Lu; Li, Xiangzhi; Guan, Yunfei; He, Hongyang (Frontiers in Oncology, 2023)
Aim: To explore whether C-reactive protein (CRP) mediates the risk of body mass index (BMI) in pancreatic cancer (PC), and calculate the mediate proportion of CRP in this possible mechanism. Methods: Based on two-sample mendelian randomization (TSMR), a two-step mendelian randomization (TM) model was conducted to determine whether CRP was a mediator of the causal relationship between BMI and PC. The multivariable mendelian randomization (MVMR) study was designed for mediating analysis and to calculate the mediating proportion mediated by CRP. Results: BMI has a positive causal relationship with PC (n=393snps, OR=1.484,95%CI:1.021-2.157, p<0.05). BMI has a positive causal relationship with CRP (n=179snps, OR=1.393,95%CI:1.320-1.469, p<0.05). CRP has a positive causal relationship with PC (n=54snps, OR=1.348,95%CI:1.004-1.809, p<0.05). After adjusted CRP, BMI has no causal relationship with PC (n=334snps, OR=1.341,95%CI:0.884-2.037, p<0.05), After adjusted BMI，there was still a positive causal relationship between CRP and PC (n=334snps, OR=1.441,95%CI: 1.064-1.950, p<0.05). The mediating effect of CRP was 29%. Conclusions: In clinical practice, while actively advocating for weight loss among obese patients, we should focus on chronic inflammation levels in obese patients as well. In addition, anti-inflammatory dietary patterns and appropriate physical activity are important in preventing PC.